Biphasic Hyalinizing Psammomatous Renal Cell Carcinoma: Another Provisional Entity Emerging From the Papillary Renal Cell Carcinoma Pandora's Box. (October 2021) - Gopinath, Arun; Mubeen, Aysha; Jamal, Mohsin; Mohammed, Ibraheem; Gopireddy, Dheeraj Reddy; Baskovich, Brett
Papillary renal cell carcinoma (especially type 2) is a Pandora's box with many newly described renal cell carcinomas emerging from it as a result of enhanced molecular techniques. Biphasic hyalinizing psammomatous renal cell carcinoma (BHPRCC) is the latest addition, which was first described a few months ago. Here, we report a case of BHPRCC to supplement the very limited literature available about this entity, and to highlight the characteristic morphology as well as the recurring molecular alterations in the neurofibromatosis 2 gene.